FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR UDANG PUTIH (PENAEUS INDICUS) INDONESIA KE HONGKONG SERTA IMPLIKASI KEBIJAKANNYA - Betrix Silitonga; Manuntun Parulian Hutagaol (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2016)
This study aimed to analyze the factors that affect the volume of Indonesian exports of white shrimp (Penaeus indicus) to Hongkong and to formulate policies that can increase the volume of exports. Ordinary Least Square method (OLS) is used to analyze the factors that affect the volume of Indonesian white shrimp exports to Hongkong by time series data (time series) period of the last 24 years (1990 until 2013). All independent variables that have significant influence on the volume of Indonesian exports of white shrimp, which are: Hongkong population, Hongkong GDP per capita constant 2005, the nominal selling price of white shrimp Indonesia to Hongkong, the nominal selling price of white shrimp competitor to Hongkong, the nominal exchange rate of the Indonesian to Hongkong and Indonesian economic crisis in 1998 (dummy). Key words: Hongkong, Ordinary Least Square (OLS), the export volume, the white shrimp (Penaeus indicus)